Curcumin attenuates angiotensin II‐induced podocyte injury and apoptosis by inhibiting endoplasmic reticulum stress. Issue 10 (28th August 2020) - Yu, Nan; Yang, Lin; Ling, Lilu; Liu, Yuan; Yu, Ying; Wu, Qing; Gu, Yong; Niu, Jianying
Abstract : Podocytes are an important component of the glomerular filtration barrier in the kidneys. The dysfunction and apoptosis of podocytes are important factors that can lead to the progression of chronic kidney disease (CKD). In CKD, angiotensin II is continuously elevated in circulation and is considered to have key roles in inducing podocyte injury and apoptosis. Curcumin is a hydrophobic polyphenolic compound extracted from turmeric. Increasing evidence demonstrates that curcumin has a protective effect on the kidneys in CKD. However, the mechanisms mediating this protective effect remain unclear. The aim of this study was to explore whether curcumin could protect against angiotensin II‐induced injury and apoptosis of podocytes. We performed western blotting, immunofluorescence, phalloidin staining, and terminal deoxynucleotidyl transferase nick‐end labeling staining to observe the expression level of podocyte‐specific proteins, apoptosis‐related proteins, and the arrangement of F‐actin. We found that curcumin could reverse angiotensin II‐induced podocyte injury and apoptosis in a dose‐dependent manner. In addition, curcumin dose‐dependently attenuated a pro‐apoptotic pathway, activated by angiotensin II‐induced endoplasmic reticulum stress. Conversely, the protective effects of curcumin were impaired upon addition of tunicamycin, an activator of endoplasmic reticulum stress. Thus, we speculate that curcumin protects against angiotensin II‐induced podocyte injury and apoptosis, at least partly by inhibiting endoplasmic reticulum stress. Abstract : Here, we show that curcumin, an active hydrophobic polyphenolic compound extracted from turmeric, could reverse angiotensin II‐induced podocyte injury and apoptosis in a dose‐dependent manner. We found this protective effect of curcumin to be at least partly achieved by inhibiting endoplasmic reticulum stress. Therefore, curcumin may have potential for future development into a possible treatment for chronic kidney disease.